Comparing semi-professional and amateur game contexts via Football Competence (Procedural Tactical Knowledge) - Rubén Sánchez-López; Ibon Echeazarra; Julen Castellano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to analyze the game context of the same task (a reduced game P+4 vs. 4+P) in two groups (8 semi-professionals and 8 amateurs), comparing the procedural tactical knowledge of the players. 1377 tactical behaviors were analyzed through the Football Competition Observation System (FOCOS), evaluating the volume and efficiency of 67 variables. Student's t-test for independent samples and Cohen's d effect size were calculated. Using the Bonferroni correction to control for the family error rate in each criterion of the observation tool, significant differences were found in 13 variables (volume, n = 1; efficiency, n = 12), with the following sizes of effect (very large = 4; large = 9). The results revealed that game contexts differ mainly in the efficiency of tactical behaviors that take place outside the game center. Based on this finding, variables focused on the relationship with the ball, widely used to assess performance in team sports, must be carefully judged when comparing players from different divisions and categories; and coaches must prioritize their attention on what happens away from the ball, instead of focusing feedback on those tactical behaviors that occur in the heat of the action. Keywords: performance, decision making, comparative analysis, observational methodology, reduced games